Prevalence of Substance Abuse among Secondary School Students in Lagos State of Nigeria - Olanrewaju Onigbogi; Omobola Ojo; Oluwatoyin Babalola (European Scientific Journal, ESJ, 2023)
Background: Substance abuse among Nigerian in-school youth has been on the rise in recent times with attendant physical and mental health consequences. This study aimed at determining the awareness and knowledge of, attitude to, and prevalence of substance abuse among senior secondary school students in Lagos State of Nigeria. Methods: This was a descriptive cross-sectional study conducted among senior secondary school students in Lagos using the multistage sampling technique. A pre-tested structured, self-administered questionnaire was used to collect data which was analyzed using Statistical Package for Social Science (SPSS) version 21. The level of significance for statistical analysis was set at p ≤0.05 at a 95% Confidence Interval. Pearson’s Chi square and Fisher's exact tests were used to determine the association between categorical variables. Results: A total of 422 students participated in the study with a mean age of 16.30 ± 1.72 years. Three hundred and seventy-eight respondents (89.6%) indicated that they were aware of substance abuse with television being the commonest first source of information, 134 (35.5%). The overall knowledge of students on substance abuse was good (66.9%) and the attitude to substance abuse was positive among 233 respondents (61.6%). The overall prevalence of substance abuse was 8.3% and the most commonly used substances were opiates such as codeine-containing cough syrup and tramadol (11.6%), followed by tranquilizers (9%), hallucinogens (5.6%) and amphetamines (5.3%) with the influencers of use being mainly family friends (31.4%), parents (22.9%) and peers (22.9%). Conclusion: The study revealed that despite overall good knowledge and positive attitudes, substance abuse remained a practice in this group. There is a need to implement school-wide positive behavioral programs to reduce prevalence and supply reduction interventions to reduce the availability of these substances. There is also a need for further studies to explore the other drivers and facilitators of this phenomenon.